(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Taman Nostalgia has served as the main public open space in Kupang City since its inauguration in 2011. Designed as a space for recreation and social interaction, the park plays a significant role in the daily lives of city residents. After 14 years of operation, a quality assessment is necessary to evaluate how well the park functions as an inclusive space for all. This study evaluates the quality of Taman Nostalgia using the Public Space Index (PSI) method, supported by a behavioral mapping analysis conducted previously (Neonufa, 2024), which provides a foundation for assessing spatial quality. The results show that the park’s average public space quality index is 63.4. The aspects of inclusiveness (75.9) and pleasurability (75.5) recorded the highest scores, while meaningful activities (56.2), safety (56.5), and comfort (52.7) indicated areas needing improvement. Overall, Taman Nostalgia is considered an inclusive public space with a strategic location, good accessibility, sufficient area, and a variety of existing activities. However, improvements are still needed in terms of activity diversity, facility provision, safety, and visitor comfort. These findings have important implications for the future design and management of public open spaces in Kupang. The combined approach of behavioral analysis and the PSI method provide comprehensive and context-responsive recommendations that address user needs and local characteristics.